Native myocardial T1 time can predict development of subsequent anthracycline‐induced cardiomyopathy. (19th April 2018) - Muehlberg, Fabian; Funk, Stephanie; Zange, Leonora; von Knobelsdorff‐Brenkenhoff, Florian; Blaszczyk, Edyta; Schulz, Alexander; Ghani, Saeed; Reichardt, Annete; Reichardt, Peter; Schulz‐Menger, Jeanette
Abstract: Aims: This study aims to assess subclinical changes in functional and morphological myocardial magnetic resonance parameters very early into an anthracycline treatment, which may predict subsequent development of anthracycline‐induced cardiomyopathy (aCMP). Methods and results: Thirty sarcoma patients with planned anthracycline‐based chemotherapy (360–400 mg/m 2 doxorubicin‐equivalent) were recruited. Median treatment time was 19.1 ± 2.1 weeks. Enrolled individuals received three cardiovascular magnetic resonance studies (before treatment, 48 h after first anthracycline treatment, and upon completion of treatment). Native T1 mapping (modified Look–Locker inversion recovery 5s(3s)3s), T2 mapping, and extracellular volume maps were acquired in addition to a conventional cardiovascular magnetic resonance with steady‐state free precession cine imaging at 1.5 T. Patients were given 0.2 mmol/kg gadoteridol for extracellular volume quantification and late gadolinium enhancement imaging. Development of relevant aCMP was defined as drop of left ventricular ejection fraction (LVEF) by >10%. For analysis, 23 complete data sets were available. Nine patients developed aCMP with LVEF reduction >10% until end of chemotherapy. Baseline LVEF was not different between patients with and without subsequent aCMP. When assessed 48 h after first dose of antracyclines, patients with subsequent aCMP had significantly lower native myocardial T1 times compared with before therapy (1002.0 ± 37.9 vs. 956.5 ± 29.2 ms, P  < 0.01) than patients who did not develop aCMP (990.9 ± 56.4 vs. 978.4 ± 57.4 ms, P  > 0.05). Patients with aCMP had decreased left ventricular mass upon completion of therapy (86.9 ± 24.5 vs. 81.1 ± 22.3 g; P  = 0.02), while patients without aCMP did not show a change in left ventricular mass (81.8 ± 21.0 vs. 79.2 ± 18.1 g; P  > 0.05). No patient developed new myocardial scars or compact myocardial fibrosis under chemotherapy. Conclusions: Early decrease of T1 times 48 h after first treatment with anthracyclines can predict the development of subsequent aCMP after completion of chemotherapy.